2012
DOI: 10.5152/akd.2012.097
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability analysis of single channel electrocardiogram can help to differentiate high- risk patients with obstructive sleep apnea syndrome - a study on diagnostic accuracy

Abstract: Heart rate variability analysis of single-channel electrocardiogram can help to differentiate high-risk patients with obstructive sleep apnea syndrome -a study on diagnostic accuracyTek kanal elektrokardiyografide kalp hızı değişkenliği analizi yüksek riskli obstrüktif uyku apne sendromlu hastaları tanımlamada yardımcı olabilir-Bir doğruluk değeri çalışması ABSTRACTObjective: To evaluate the usefulness of heart rate variability analysis (HRV) analysis from the long duration electrocardiogram (ECG) recordings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…LF has been associated with changes in blood pressure along with fluctuations in sympathetic and parasympathetic activity. VLF has been related to alterations in body temperature and sleep apnea-related heart rate changes 39. ULF has been associated with circadian rhythms 40…”
Section: The Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…LF has been associated with changes in blood pressure along with fluctuations in sympathetic and parasympathetic activity. VLF has been related to alterations in body temperature and sleep apnea-related heart rate changes 39. ULF has been associated with circadian rhythms 40…”
Section: The Reviewmentioning
confidence: 99%
“…They are computed based upon newer bioengineering developments, incorporating theories of complexity, chaos, and fractal characteristics 3944. These methods may capture information about underlying patterns of physiological variability (such as how random or correlated the signals are) beyond that which time and frequency domain measurements can offer 2,44…”
Section: The Reviewmentioning
confidence: 99%
“…Studies have shown that changes in heart rate variability (HRV) can be potentially used as an alternative technique to screen children with OSAHS (Park et al 2008;Chaicharn et al 2009;Balachandran et al 2012;Lado et al 2012;Sforza et al 2012;Song et al 2012). Studies have also confirmed the feasibility of screening OSAHS in adults by HRV analysis (Roche et al 1999;Poupard et al 2011;Sun et al 2011;Karasulu et al 2012). Hence, this study aimed to evaluate the performance of this simple tool in the monitoring of snoring children who were referred to the Sleep Center of Beijing Children's Hospital for OSAHS diagnosis.…”
Section: Introductionmentioning
confidence: 91%
“…OSAS patients often suffered from enhanced sympathetic nervous system activation by chemoreceptors and baroreceptors in response to recurrent apnea, hypoxemia, and hypercapnia and previous studies have found that some HRV variables were significantly different between patients with OSAS and without, confirming the feasibility of HRV analysis to screen OSAS. Studies have pointed out that appropriate HRV variable with reasonable threshold has certain sensitivity and specificity, however, difference is very big between different research results, not only the HRV variable but also the threshold (Roche et al 1999;Roche et al 2004;Vazir et al 2006;Sun et al 2011;Karasulu et al 2012). The main causes may be different groups who participated, different diagnosis standard of OSAS, different method of recording and analyzing ECG (Electrocardiograph) data.…”
Section: Capacity Of Screening Osahs By Hrv Analysismentioning
confidence: 96%
“…Este incremento puede atribuirse a los episodios de braditaquicardia secuentes a las apneas que presentan estos pacientes. Este aspecto concuerda con lo previamente descrito en la literatura [135,159]. Taranto-Montemurro et al, destacan que los pacientes con síndrome overlap tienen mayor activación simpática del SNA durante el día en comparación con aquellos con diagnóstico exclusivo de SAHS o de EPOC [167].…”
Section: Análisis Espectralunclassified